TATA KELOLA SDM DI ERA E-LAND ADMINISTRATION: PENGUATAN KAPABILITAS DAN SISTEM DIGITAL UNTUK DATA PERTANAHAN - Setyo Gunawan (CV. ADIBA AISHA AMIRA, 2025)
Digital transformation in land administration (e-Land Administration) is the main strategy to increase transparency, efficiency, and accountability of public services. However, the success of its implementation does not only depend on technology, but also on human resource (HR) governance which plays a central role in operating and supervising digital systems. This study uses a qualitative approach with the systematic literature review (SLR) method to analyze the role of human resources in supporting land digitalization. Data was collected from internationally reputable publications through databases such as Scopus, ScienceDirect, and Taylor & Francis, and then analyzed using thematic analysis techniques. The results of the study show that technical competence, digital literacy, and institutional readiness of human resources are key factors in ensuring the effectiveness of e-Land Administration. In developing countries such as Indonesia, the main obstacles lie in regulatory gaps, limited human resource capacity, and bureaucratic cultural resistance to change. The study also found that the integration of cutting-edge technologies such as artificial intelligence (AI), blockchain, and cloud computing will only be effective if supported by skilled and adaptive human resources. This study concludes that digital-based land administration reform requires continuous investment in capacity building, regulatory strengthening, and responsive institutional design. These findings have implications for the need for a policy strategy that places human resources at the center of e-Land Administration success, so that digitalization can function not only as a technical innovation, but also as an instrument of fair and sustainable governance.